A DPL model of photothermal interaction in a semiconductor material. Issue 2 (3rd April 2019) - Abbas, Ibrahim A.; Alzahrani, Faris S.; Elaiw, Ahmed
ABSTRACT: The generalized model for plasma, thermal, and elastic waves under dual phase lag model have been applied to determine the carrier density, the displacement, the temperature, and the stresses in a semiconductor medium. Using Laplace transform and the eigenvalue approach methodology, the solutions of all variables have been obtained analytically. A semiconducting material like as silicon was considered. The results were graphically represented to show the different between the dual phase model, Lord and Shulman's theory and the classical dynamical coupled theory.